Promoting community health collaboration between CTSA programs and Cooperative Extension to advance rural health equity: Insights from a national Un-Meeting. Issue 5 (13th October 2020) - Gutter, Michael S.; O'Neal, LaToya J.; Riportella, Roberta; Sugarwala, Laura; Mathias, John; Vilaro, Melissa J.; Paige, Samantha R.; Szurek, Sarah M.; Navarro, Giselle; Baralt, Claire; Rhyne, Robert
Abstract: Addressing rural health disparities has unique challenges that require cross-sector collaborations to address social determinants of health and help those in need to get connected to care continuum. We brought the Clinical and Translational Science Award, Institutional Development Award Program Infrastructure for Clinical and Translational Research, and Cooperative Extension System Programs together for a one-day semi-structured meeting to discuss collaborative opportunities to address rural health disparities. Session notes and event materials were analyzed for themes to facilitate collaboration such as defining rural, critical issues, and organizational strengths in support of collaboration. Across 16 sessions, there were 26 broad topics of discussion. The most frequent topics included "barriers and challenges, " "strategies and opportunities, " and "defining rural." There is a growing understanding of the opportunity that collaboration between these large programs provides in addressing rural health disparities.